Application of Process Modeling in a Software- Engineering Course - Gabriel Alberto García Mireles; Josefina Rodríguez Jacobo (Universidad Autónoma de Baja California, 2001)
Coordination in a software development project is a critical issue in delivering a successful software product, within the constraints of time, functionality and budget agreed upon with the customer. One of the strategies for approaching this problem consists in the use of process modeling to document, evaluate, and redesign the software development process. The appraisal of the projects done in the Engineering and Methodology course of a program given at the Ensenada Center of Scientific Research and Higher Education (CICESE), from a process perspective, facilitated the identification of strengths and weaknesses in the development process used. This paper presents the evaluation of the practical portion of the course, the improvements made, and the preliminary results of using the process approach in the analysis phase of a software-development project.